2017
DOI: 10.1016/j.jbtep.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and emotional processing of pleasant and unpleasant experiences in major depression: A matter of vantage point?

Abstract: Both people suffering from MD and healthy individuals may benefit from processing pleasant experiences, especially when adopting a self-distant perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…(Craske et al, 2019;Dunn, 2019;Geschwind, Arntz, Bannink, & Peeters, 2019;Sewart et al, 2019). Reflecting on the Best Possible Self (rather than recalling positive memories) may be a particularly effective way of stimulating positive affect for people with heightened psychopathology, given that a recent study found that adopting a more analytic, reflective perspective (rather than merely recounting positive events) led to increased improvements in both PA and NA for individuals with major depression (Pfaltz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(Craske et al, 2019;Dunn, 2019;Geschwind, Arntz, Bannink, & Peeters, 2019;Sewart et al, 2019). Reflecting on the Best Possible Self (rather than recalling positive memories) may be a particularly effective way of stimulating positive affect for people with heightened psychopathology, given that a recent study found that adopting a more analytic, reflective perspective (rather than merely recounting positive events) led to increased improvements in both PA and NA for individuals with major depression (Pfaltz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In light of emerging research that depression is associated with deficits in voluntarily recalling positive imagery (Holmes et al, ; Weßlau & Steil, ), further research is also needed to understand if depression is associated with the absence of involuntarily recalled positive memories. Furthermore, as individuals with depression, as well as healthy controls, report a decrease in negative affect and an increase in positive affect when voluntarily recalling and analysing positive experiences, particularly when using the observer perspective (Pfaltz et al, ), further research could examine how analysing involuntary positive memories, while adopting a self‐distant perspective, influences affect and depressive symptomatology. It is also unclear how intrusive memories compare with other imagery‐based cognitions such as future‐oriented mental images of suicide, which have been reported in depression (Holmes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, analysing negative feelings from a self‐distanced perspective resulted in an adaptive shift in the way individuals interpreted their experience. Pfaltz et al () similarly found that a third‐person (observer) perspective was associated with less recounting of negative experiences and assisted both depressed and healthy individuals to develop a clearer, more coherent understanding of their experience. It is unclear if these patterns also occur when the past experiences are recalled and processed involuntarily.…”
Section: Introductionmentioning
confidence: 99%